2022
DOI: 10.1111/een.13202
|View full text |Cite
|
Sign up to set email alerts
|

Strong influence of leaf tie formation and corresponding weak effect of leaf quality on herbivory in eight species of Quercus

Abstract: 1. Leaf shelter construction by herbivorous insects can improve leaf quality, sometimes changing resultant herbivory. In two experiments in a Missouri (USA) deciduous forest we quantified the impact of leaf tie construction and changes to leaf quality on subsequent leaf damage.2. First, using eight Quercus species, we compared damage to single leaves versus experimental leaf ties that had been stocked with either Pseudotelphusa quercinigracella (Gelechiidae) or Psilocorsis cryptolechiella (Depressariidae) to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Penetrometers are usually used for determining the texture and firmness of fruits, [12,13] but some studies have also shown the use of penetrometers, which should provide objective data compared to tasters, to determine the toughness and texture of the leaves. Takeuchi and Zalucki [16] used a penetrometer to determine Eucalyptus leaf toughness; Wang et al [17] and Salgado-Luarte et al [18] measured the leaf toughness of different spp. of oak trees and 11 spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penetrometers are usually used for determining the texture and firmness of fruits, [12,13] but some studies have also shown the use of penetrometers, which should provide objective data compared to tasters, to determine the toughness and texture of the leaves. Takeuchi and Zalucki [16] used a penetrometer to determine Eucalyptus leaf toughness; Wang et al [17] and Salgado-Luarte et al [18] measured the leaf toughness of different spp. of oak trees and 11 spp.…”
Section: Discussionmentioning
confidence: 99%
“…The penetrometer is usually used to determine the texture of fruits, for example, apples and strawberries [12,13]. However, some studies have also shown the use of a penetrometer to determine the toughness and texture of the leaves [15][16][17][18][19].…”
Section: Determination Of Leaf Texture/toughnessmentioning
confidence: 99%
“…Third, plant traits can modify the attraction of colonists from off the plant, after it has been colonized by shelter builders (Lill and Marquis 2004 ). Finally, shelter building may modify the quality of leaves in shelters, via local induction, and in so doing, influence their use by the herbivore component of colonizers (Sagers 1992 ; Fukui et al 2002 ; Wang et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%